100 Years of Chalky Teeth Research: From Pioneering Histopathology to Social Good - Hubbard, Michael J.; Perez, Vidal A.; Ganss, Bernhard (Frontiers in Dental Medicine, 2021)
One hundred years ago, histopathology pioneer Bernhard Gottlieb described developmentally disrupted teeth as having "chalky enamel" and "chalky spots" that "crumble" easily. He also asked pivotal questions about the pathogenesis of "enamel hypoplasia" that remained enigmatic for almost a century. Today, breakthrough pathomechanistic investigations of chalky enamel are revealing surprising answers, and an allied translational initiative – The D3 Group for developmental dental defects (D3s) – is converting such scientific knowledge into social good. Molar hypomineralisation (MH) affects 1-in-5 children worldwide and is well-evidenced, but poorly recognised, as a principal risk factor for childhood tooth decay. Given MH is causally linked to infantile illness, an exciting corollary is that medical prevention would lead to substantial reductions in tooth decay. Here we reflect on the past century of chalky teeth research and retrace the path leading to recognition of MH as a global health concern. Five research eras, today's four major D3s, and diverse experimental attacks are outlined alongside translational wins that have benefitted global health. Addressing hopes for medical prevention of MH, this centennial year's pathomechanistic discovery is contextualised against past accomplishments and new opportunities. Finally, we note the translational value of accessible infographics for guiding future work, and forecast exciting prospects for the next century.